Evaluasi Kinerja Petugas Koding Dan Klaim Jkn Rawat Inap di RSUP dr. Hasan Sadikin Bandung - Nur Amaliyatul Fadlilah; Efri Tri Ardianto; Sustin Farlinda (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Performance is a work that can be achieved by a person or a group of people in one organization, inaccordance with the authority and responsibilities of each, in order to achieve organizational goals. Thefactors that affect performance are motivation, opportunity, ability. Based on the results of a preliminarystudy at RSUP Dr. Hasan Sadikin, Bandung, the performance of the coding officer and JKN claims wereconsidered to be less than optimal, because there were still many medical record files that were not yetencoded. Resulting in a delay in BPJS payments to hospitals. The purpose of this study was to evaluate theperformance of the coding officer and JKN claims for inpatients at Dr. RSUP. Hasan Sadikin Bandung. Thistype of research is a qualitative study by describing the situation at the time of the study with the aim ofproviding a clear picture of the performance of the coding officer and inpatient JKN claims. The results ofthis study were the first results coding officers and inpatient JKN claims never get a reward from theleadership let alone get praise and certificates of appreciation for their performance in accordance withexisting procedures. Both the coding officer and the inpatient JKN claim have attended training and 3seminars on medical records especially about codification. Thirdly, the existence of SPO regarding theimplementation of coding and claims of JKN is hospitalized so that it can facilitate the officers in carrying outtheir duties.